A customizable 3D printed device for enzymatic removal of drugs in water. (1st January 2022) - Xu, Xiaoyan; Pose-Boirazian, Tomás; Eibes, Gemma; McCoubrey, Laura E.; Martínez-Costas, Jose; Gaisford, Simon; Goyanes, Alvaro; Basit, Abdul W.
Highlights: A 3D printed biocatalytic device (termed Printzyme) is proposed for enzymatic removal of drugs from water. Laccase was immobilised within a poly(ethylene glycol) diacrylate hydrogel using stereolithography 3D printing. The Printzyme is customizable, highly reusable, and cost-efficient. 95% of diclofenac and ethinylestradiol from aqueous solution were removed within 24 and 2 h, respectively. Abstract: The infiltration of drugs into water is a key global issue, with pharmaceuticals being detected in all nearly aqueous systems at often alarming concentrations. Pharmaceutical contamination of environmental water supplies has been shown to negatively impact ecological equilibrium and pose a risk to human health. In this study, we design and develop a novel system for the removal of drugs from water, termed as Printzyme. The device, fabricated with stereolithography (SLA) 3D printing, immobilises laccase sourced from Trametes Versicolor within a poly(ethylene glycol) diacrylate hydrogel. We show that SLA printing is a sustainable method for enzyme entrapment under mild conditions, and measure the stability of the system when exposed to extremes of pH and temperature in comparison to free laccase. When tested for its drug removal capacity, the 3D printed device substantially degraded two dissolved drugs on the European water pollution watch list. When configured in the shape of a torus, the device effectively removed 95% of diclofenac and ethinylestradiol from aqueous solution within 24 and 2 h, respectively, more efficiently than free enzyme. Being customizable and reusable, these 3D printed devices could help to efficiently tackle the world's water pollution crisis, in a flexible, easily scalable, and cost-efficient manner. Graphical abstract: Image, graphical abstract